Tingkat Kepuasan Konsumen Pada Kairos Cafe Di Desa Rasi Kecamatan Ratahan Kabupaten Minahasa Tenggara - Pontororing, Juwita Petricia; Manginsela, Elsje Pauline; Benu, Noortje Marselianie (AGRI-SOSIOEKONOMI, 2023)
This research aims to determine the level of consumer satisfaction with products, prices, places, promotions and services. The research was carried out from May to July 2023. The data collection method used was primary and secondary data. Respondents in this study consisted of 42 people who were selected using accidental sampling techniques. Data was measured using a Likert scale, then analyzed using the Consumer Satisfaction Index. The research results show that Kairos Cafe's consumer satisfaction level is classified as very satisfied with a consumer satisfaction index of 86.00%. More specifically for each aspect, the level of satisfaction with the product is 86.50%, price is 86.66%, place is 87.14%, promotion is 84.76%, and service is 85.07% which are classified as very satisfied.